Code-Mixing and Code-Switching in Online Teaching - Natan Barus; Rahmadsyah Rangkuti; Umar Mono (Jurnal Pendidikan dan Pengajaran, 2024)
Problems that often occur in learning need to be clarified when communicating. This is related to the use of code-mixing and connection switching in learning. This research aims to analyze the types of code-switching and code-mixing in online teaching, how English teachers use code-switching and code-mixing, and why teachers switch and mix speech. This research was conducted using a qualitative descriptive design. The objects of this research were three English teachers. Data was collected via Zoom video recording of the teacher's speech. Data were analyzed using the Miles, Huberman, and Saldana interactive model. The research results show that the type of code-switching teachers do most often is inter-sentential code-switching. There are 51 types, with a percentage of 50.49%. The code-mixing that teachers most often do is inserting (words). The total is 71 types, with a percentage of 70.29%. Finally, the most common reason teachers change and mix codes in speech is clarification of the content of speech, and the number is 8 with a percentage of 29.62%.